Peran Kualitas Produk Dan Harga Terhadap Loyalitas Konsumen Dengan Kepuasan Sebagai Variabel Intervening (Pada Mahasiswa Yang Berdomisili Di Kelurahan Merjosari, Malang) - Nur Syahraini; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2020)
AbstractConsumers generally buy a product that is truly in accordance with their needs and desires. In addition, consumers buy a product or service adjusting the price with the quality of products offered by a company or online store site to achieve a satisfaction and loyalty. The price and quality of the products provided is the most important component by the company for consumer satisfaction. Companies must pay attention to important things for consumers, so they feel the expected satisfaction. The main thing in satisfaction and loyalty is the quality of the product and the price offered. In addition, loyalty also provides a very large profit for the company, because it affects customer buying patterns and supports what customers give to others. This study aims to determine the price and quality of products that directly affect customer loyalty through customer satisfaction as an intervention variable. The purpose of this study : a) To determine the price determined customer loyalty. b) To find out the quality of the prosucts approved for consumer loyalty. c) To understand customer satisfaction. d) To find out the suggested price and product quality on customer loyalty through customer satisfaction as an intervening variable. The type of research is quantitative. Methods of data collection using a questionnaire and observation. The population in this study took data obtained from students who live in the village of Merjosari, Malang as many as 480 respondents, with a sample in this study obtained 83 respondents. Data analysis methods used were instrument testing, normality testing, path analysis (Path Analysis), and hypothesis testing using SPSS v16 tools. The results in this study indicate that positive and significant prices on consumer loyalty and product quality are positive and significant on consumer loyalty by value (0,000) and there is a relathionship between product quality and customer satisfaction as an intervening variable relationship to customer loyalty with a value of one tailed probability (0,0). Keywords : Price, Product Quality, Consumer Satisfaction, Consumer Loyalty.